-3(x-6)(2x+3)=0

Simple and best practice solution for -3(x-6)(2x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-6)(2x+3)=0 equation:



-3(x-6)(2x+3)=0
We multiply parentheses ..
-3(+2x^2+3x-12x-18)=0
We multiply parentheses
-6x^2-9x+36x+54=0
We add all the numbers together, and all the variables
-6x^2+27x+54=0
a = -6; b = 27; c = +54;
Δ = b2-4ac
Δ = 272-4·(-6)·54
Δ = 2025
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{2025}=45$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(27)-45}{2*-6}=\frac{-72}{-12} =+6 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(27)+45}{2*-6}=\frac{18}{-12} =-1+1/2 $

See similar equations:

| 3y+4-y+1=3-4y | | 2(x-3)^2=60 | | -21=8n-n | | 8/12=a | | -5(4b-6)-7=163 | | 2x2+13x=21 | | -7(-3p-6)-2p=137 | | 6-6(-2x+7)=-4(x-3) | | (x-2)^2+16=66 | | -7(3p-6)-2p=137 | | 5z+2=3z-5 | | -259=-7(5k-3 | | 7w-7+5w+1+90=180 | | 80+70+x+2x+2x+3x=360 | | -250=-5(7b-6) | | 55+9r-1+90=180 | | 0.5r-3r+5=0 | | 3x/2-6=9-x/2 | | 18m-20=34 | | 5x²+13x=6 | | x/6+x/4=10 | | -16-16x=48+8x | | 2(9^x-3)=162 | | 8(d+8=2(d-5)+6d | | 8(2m+3)+14m+15=-21 | | 9t=73 | | 15/x=8/x-6 | | A+5=1/3(3a+15) | | 2b=8b-18 | | 10+2v=4v-6 | | 36=(9x+5) | | 2b=8b=18 |

Equations solver categories